Beta fuzzy logic systems: Approximation properties in the SISO case - Alimi, Adel M.; Hassine, Radhia; Selmi, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a Single-Input Single-Output (SISO) Sugeno fuzzy model of the zeroth order with Beta membership functions for input variables is adopted. After the introduction of Beta Fuzzy Logic Systems (BFLS) a constructive theory is developed to establish the fact that they are universal approximators. Based on this theory, an algorithm, which can actually construct a BFLS approximating a given continuous function with an arbitrary degree of accuracy, is described.
Keywords: Beta function; universal approximation property; best approximation property; interpolation property; Sugeno fuzzy model; SISO systems